Role of Serum Alkaline Phosphatase and Osteocalcin in Predicting Bone Healing after Internal Fixation of Long Bone Fractures - Muhammad Qaiser Faheem, Salman Habib Abbasi, Hassan Raza Heral, Parvez Ahmed, Furqan Haseeb, Muhammad Yousuf Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bone healing is a complex biological process that depends on coordinated cellular and biochemical mechanisms. Traditional radiographic evaluation often fails to reflect early biological healing. Therefore, biochemical markers such as serum alkaline phosphatase (ALP) and osteocalcin (OC) may serve as valuable indicators of osteoblastic activity and bone regeneration. This study aimed to assess the predictive role of ALP and OC in monitoring bone healing following internal fixation of long bone fractures. Methods: A prospective observational study was conducted from June 2022 to May 2023 at the Department of Orthopedic Surgery, Social Security Hospital, Shahdara, Lahore, in collaboration with the Department of Radiology, Gambat Institute of Medical Sciences, Sindh. A total of 150 patients aged 18–65 years with long bone fractures managed by internal fixation were included. Serum ALP and OC levels were measured preoperatively and at 4, 8, and 12 weeks postoperatively. Radiographic healing was evaluated using the Radiographic Union Scale for Tibial fractures (RUST), and correlations between biochemical markers and healing scores were analyzed. Results: Both ALP and OC levels increased significantly during the healing period (p < 0.001). ALP peaked at 8 weeks (129.7 ± 18.8 IU/L), while OC showed a steady rise up to 12 weeks (28.7 ± 7.1 ng/mL). Osteocalcin demonstrated a stronger correlation with RUST scores (r = 0.72, p < 0.001) than ALP (r = 0.66, p < 0.01). Patients with higher OC and ALP values showed faster and more complete union at 12 weeks. Conclusion: Serial measurement of serum ALP and osteocalcin provides a reliable, non-invasive method to predict and monitor bone healing following internal fixation of long bone fractures, with osteocalcin serving as a more sensitive marker of late-stage bone formation. Keywords: Alkaline phosphatase, Osteocalcin, Bone healing, Internal fixation, Long bone fractures, Biochemical markers.